The Impact of Sexual Harassment in Ugandan Sports - Martin Otim (Uganda Christian University, 2024)
This thesis analyses the presence of the vice of sexual harassment in the sports field of uganda as it clearly provides the greater need of the laws to strengthen the rights of athletes in ugandan sports because there is serious damage that is impacted to them and of which this leads to greater weakness in their minds and generates poor results and this vice is slowly increasing and with much emphasis it can be erased throughout sports sector in uganda